Assessment of an international breaststroke swimmer using the 7 × 200-m step test - Thompson, K.; Garland, S.; Lothian, F. (International Journal of Sports Physiology and Performance, 2006)
Thompson and Cooper observed that improvements in the swimming speed at 2-mM and 6-mM lactate concentration coincided with improvements in competitive breaststroke performances, whereas Pyne et al concluded that changes in swimming speed at lactate threshold were not directly associated with competition performances in a mixed-stroke group of 12 elite swimmers. This case study presents data from eleven (7 × 200 m) step tests over a 3-year period for a world-class 200-m male breaststroke swimmer. Personal-best race times were reduced by 9.5 seconds over this period. For this individual, step-test data provided valuable information with regard to the swimmer`s readiness for performance, health and training status, and nutritional habits.